"Managing for Outcomes" in the New Zealand Public Management System - Anna-Luis Cook (New Zealand Government, The Treasury, 2004)
Managing for Outcomes is the process by which central agencies and Ministers are seeking to promote a results focus within the New Zealand public management system. This paper argues that if a results focus is to truly be introduced to the New Zealand public management system then all aspects of the wider system will need to be amended, in order to support a general cultural change. In promoting this view the paper provides a summary of the system as it currently stands and considers how the structural, financial, strategic and performance management elements of the wider public management system could be amended to support an outcomes focus within the core New Zealand public service.
Keywords: D29; D73; H19; 330; New Zealand; public sector management; government